Assessment of Nutritional Status and Related Factors of Lactating Women in the Urban and Rural Areas of Southwestern Iran: A Population-Based Cross-Sectional Study Abstract - Mahnaz Mardani; Amir Abbasnezhad; Farzad Ebrahimzadeh; Sajjad Roosta; Maryam Rezapour; Razieh Choghakhori (Shiraz University of Medical Sciences, 2020)
Background: During the lactation period, mothers are at an increased risk of nutritional deficiencies due to improper dietary patterns, physiological changes, and various socio-demographic factors. The present study aimed to examine the nutritional status, dietary intake, and related factors among lactating women in the urban and rural areas of Khorramabad, Lorestan province in the southwest of Iran. Methods: The present population-based cross-sectional study was conducted in Khorramabad (Iran) during April-July 2012. The study population included 708 lactating mothers who were referred to the health centers in Khorramabad (10 urban health centers and 30 rural health/community centers). A multi-stage sampling method was used to recruit the participants. The nutritional status and food intake of the participants were assessed over three days using the 24-hour dietary recall (24HDR) and dietary record (DR) questionnaires. The data were analyzed using SPSS software (version 16.0) with the Chi-square test, Fisher's exact test, paired t test, independent t test, and Pearson correlation coefficient. PResults: The mean age and body mass index (BMI) of the mothers were 29.78±6.24 years and 26.11±3.70 kg/m2, respectively. There was a significant difference in calorie intake between the different categories of age, BMI, education level, job status (P<0.001) and lactation stage (P=0.034). The energy and nutrient intakes, except iron and phosphor, were statistically lower (P<0.05) than the prescribed Recommended Dietary Allowances (RDA). The intake of vitamins K, B1, B2, B3, and C; protein, magnesium, phosphor, zinc, copper, and iodine by mothers in the rural areas was significantly higher (P<0.05) than those in the rural areas. Higher intakes of energy and macronutrients by the lactating mothers had a significant negative correlation with an increase in age and had a significant positive correlation with a higher BMI (P<0.001). Conclusion: Lactating women in the urban and rural areas of Khorramabad (Iran) had a poor nutritional status. Nutrition education and a modified dietary pattern during the lactation period are recommended.